(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
By the interaction of a symmetric bis-aldehyde with 1-phenyl-3-methylpyrazolone-5, a new symmetrical dye capable of photoinduced isomerization was obtained. Recording media (RM) based on synthesized dye and soft polymer matrix were prepared. Intensity of absorption of RM rises with increasing of dye percentage in polymer matrix. But, Beer-Lambert law is not fulfilled. Therefore, the partial aggregation of dye molecules is present. As in the case of azo-compounds, information recording proceeds, probably, through spatial changes caused by the photoinduced E,Z double bond isomerization. Recorded holograms have the polarization nature – it was proved by the quenching of diffraction orders during changing the polarization of reference beam from е1┴е2 to е1║е2. It was shown that compounds containing the –НС=С< bond, where =С< is the part of heterocyclic moiety are able to the isomerization. The diffraction efficiency is expected to be higher due to presence of two photoactive groups in symmetric molecule, comparing with molecules with one photoactive group. Light absorption with λ=532 nm by the dye molecules is proved to be sufficient for holograms recording and relaxation despite the low adsorption intensity at such wavelength. The recording and relaxation speed are high. Fast increasing of h in the beginning of hologram exposition and, after turning off the illumination beam, fast decay, according to the h||(t) and h┴(t) curves. Hence, this polymer composite is capable for further applications in dynamic holography. It was shown that increasing of dye amount in polymer matrix leads to growth of diffraction efficiency. It has been established that data recording media is characterized by higher values of diffraction efficiency with parallel polarization compared to perpendicular.